2022
DOI: 10.1186/s12909-022-03124-0
|View full text |Cite
|
Sign up to set email alerts
|

To debate or not to debate? Examining the contribution of debating when studying medical ethics in small groups

Abstract: Background Medical ethics is a significant learning topic for medical students, and often studied through small group learning (SGL) to encourage critical thinking (CT) and tolerance for ambiguity, both considered particularly important when coping with medical ethics dilemmas. However, a previous study about CT and tolerance for ambiguity in medical ethics SGL produced mixed results. Debating is a pedagogical tool known to enhance CT but never used before in medical ethics learning. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
1
1
0
1
Order By: Relevance
“…Students were assigned a side to defend which compelled some students to make arguments different from their own perspective. Our finding resonates with existing literature which has suggested that the use of debates can be an effective tool for teaching medical ethics because it increases students’ critical thinking expression and tolerance toward ambiguity [ 38 ]. In addition, the reflective writing time was integrated into the session module which encouraged more valuable, thorough, and accurate feedback.…”
Section: Discussionsupporting
confidence: 88%
“…Students were assigned a side to defend which compelled some students to make arguments different from their own perspective. Our finding resonates with existing literature which has suggested that the use of debates can be an effective tool for teaching medical ethics because it increases students’ critical thinking expression and tolerance toward ambiguity [ 38 ]. In addition, the reflective writing time was integrated into the session module which encouraged more valuable, thorough, and accurate feedback.…”
Section: Discussionsupporting
confidence: 88%
“…Para la aplicación de metodologías de debate se deben tener competencias específicas como una buena comunicación oral y pensamiento crítico, estas habilidades requieren de una mayor prioridad dentro del proceso educativo dados los nuevos requerimientos del mercado actual, teniendo como método más efectivo los debates estudiante-estudiante [3]. Fomentar y mejorar el pensamiento crítico mediante grupos pequeños es de gran importancia para la formación de profesionales con ética y compromiso puesto que las habilidades del pensamiento crítico permiten al profesional abrirse ante nuevas posibilidades sin enfrascarse dentro de las mismas alternativas [4]. Adicionalmente, presentar dos personas exponiendo ideas frente a una audiencia requiere de competencias de comunicación oral y pensamiento crítico que son desarrolladas con la práctica constante de debates basados en la evidencia y la lógica para inducir al público a tomar una postura [5].…”
Section: Estado Del Arteunclassified
“…In medicine, for example, the ethical dilemmas of medical practice serve as scenarios that contribute to the development of critical thinking. 17 On the other hand, information and communication technologies (ICT) make it possible to create simulated contexts in digital environments that help to give meaning to the problems to be solved, as these technologies facilitate the design of educational experiences with the introduction of new digital narratives through visual, auditory, and/or sensory languages. 18 University students recognize the enormous potential of ICTs to support their learning and improve their academic performance, 19 so they should be considered as part of any proposal to improve teaching and learning processes at the university.…”
Section: Introductionmentioning
confidence: 99%